1988
DOI: 10.1161/01.hyp.11.6.563.a
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial communication. State of the art lecture.

Abstract: SUMMARY By virtue of its location at the interface of flowing blood and vascular tissue, the endothelial cell monolayer is in a unique position for interactions with soluble and cellular elements of the blood on one side and with component cells of the vascular tissue on the other. This brief review outlines humoral and contact-mediated endothelial communication with other cells, particularly the resident cells of the vessel wall. Evidence for gap junctional communication channels between endothelium and vascu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0

Year Published

1992
1992
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(31 citation statements)
references
References 52 publications
0
31
0
Order By: Relevance
“…Moreover, evidence has been reported suggesting that the process of relaxation involves hyperpolarization of endothelial cells (Edwards et al, 1998; and consequent gap junctional transmission between endothelium and smooth muscle, resulting in smooth muscle hyperpolarization and relaxation (Davies et al, 1988;Beny, 1990;Chaytor et al, 1998). Regardless of the con¯icting evidence for the proposed candidates, there is consensus that EDHF responses are mediated by an increase in K + conductance and thus are sensitive to depolarizing solutions of K + (Adeagbo & Triggle, 1993;Corriu et al, 1996a) and by inhibitors of certain types of K + channels.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, evidence has been reported suggesting that the process of relaxation involves hyperpolarization of endothelial cells (Edwards et al, 1998; and consequent gap junctional transmission between endothelium and smooth muscle, resulting in smooth muscle hyperpolarization and relaxation (Davies et al, 1988;Beny, 1990;Chaytor et al, 1998). Regardless of the con¯icting evidence for the proposed candidates, there is consensus that EDHF responses are mediated by an increase in K + conductance and thus are sensitive to depolarizing solutions of K + (Adeagbo & Triggle, 1993;Corriu et al, 1996a) and by inhibitors of certain types of K + channels.…”
Section: Discussionmentioning
confidence: 99%
“…Subconfluent cultures of HUVSMCs were labeled with PKH26 (Red Fluorescent General Cell Linker Kit; Sigma Chemical Co., St. Louis, MO). 2 ϫ 10 7 HUVSMCs suspended in diluent C were mixed 1:1 with 4 M PKH26 in diluent C, incubated at 25 Њ C for 5 min. FCS (2 ml) was added to the sample, and was incubated for 1 min.…”
Section: Methodsmentioning
confidence: 99%
“…Human vascular smooth muscle cells only express Cx43 and Cx40 (5,6). Functional myoendothelial gap junctional coupling has been observed in a number of studies (7)(8)(9). Since endothelial cells are located at the interface between the blood and vascular tissue, they may act in the transfer of circulatory signals to subendothelial cells by the GJIC of second messenger molecules.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been well established that SMCs exhibit a remarkable capability to transform between ''contractile'' and ''synthetic'' phenotypes and a continuum of states in between (Halayko and Solway, 2001). Moreover, the transformation can be modulated by mechanical factors like stretch and shear stress (Davies et al, 1988). Recently, a study in our laboratory demonstrated that VSMCs can react to gravity alteration at the single cellular level.…”
Section: Introductionmentioning
confidence: 99%